Commitment as a Mediator of the Relationship between Training, Job Stress, ISM Code, and Ship Crew Performance - Alwi Sibali; Ansar; Gunawan; Umi Farida (Journal of Indonesian Scholars for Social Research, 2026)
This study examines the relationship between training, job stress, and the International Safety Management (ISM) Code and ship crew performance, with commitment positioned as a mediating variable. The research was conducted at SKOM Sdn. Bhd. (SK Offshore & Marine) in Malaysia and focused on ship crews working on 10 offshore vessels. A quantitative approach was employed using a descriptive and confirmatory design. The study involved 213 crew members as respondents. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS and SPSS version 22. The findings reveal that commitment plays a significant mediating role in linking training, job stress, and ISM Code implementation to ship crew performance. Training contributes to better performance when it strengthens crew commitment and supports technical readiness in demanding maritime operations. Job stress, although often viewed as detrimental, becomes more manageable when organizational commitment is maintained, allowing crew members to remain focused on their responsibilities. Likewise, the implementation of the ISM Code enhances performance not only through compliance with safety procedures but also through its capacity to foster a stronger sense of responsibility and commitment among crew members. These results indicate that commitment is a central mechanism through which organizational and operational factors influence performance in the maritime sector. The study recommends strengthening technical training, improving workload distribution, providing mental and emotional support, and ensuring consistent implementation of safety management procedures to enhance ship crew performance.